ANALISIS SISTEM REKRUTMEN TENAGA KERJA PADA CV. MITRA SEJATI DI SAMARINDA - Aljazair, Andy (EKONOMIA, 2013)
ABSTRACTANDY, Manpower Recruitment System Analysis at CV. Mitra Sejati in Samarinda. Under the guidance of Mr. and Mrs. Eddy Soegiarto K and Eka Yudhyani. This study aims to determine the recruitment system at CV. Mitra Sejati in Samarinda. Problem formulation in this study is: